The Issue of Introdusing the Musical Traditions of Kasakhstan to the Junior School Children - L. V. Dobrovolskaya (Russian State Vocational Pedagogical University, 2015)
The paper raises the urgent issue of ethno-cultural education and looks at the process of familiarizing the junior schoolchildren with the profound musical traditions of Kazakhstan. The advantages and disadvantages of music teaching are observed with the reference to the surveys of music teaches from several towns and extramural students at North Kazakhstan State University. The surveys reveal the high level of teachers' ethno-cultural awareness, and, on the other hand, - the lack of knowledge concerning the instrumental performance, improvising, dialogism and competitiveness. The author maintains that the acquaintance with the national musical traditions should be based on the complex of reproductive, productive and perceptual activities. In order to fill up the content gaps in the curriculum and overcome the limitations of ethnical education the methodological support of school teaching should be reinforced by the theoretical developments and practical recommendations.